IMPLEMENTASI PEMBERIAN BANTUAN HUKUM KEPADA MASYARAKAT MISKIN OLEH ORGANISASI BANTUAN HUKUM DI PROVINSI GORONTALO - Ira Pakaya; Ibrahim Ahmad; Robby Waluyo Amu (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2025)
This study aims to examine and analyze the role of Legal Aid Organizations (OBH) in providing legal aid services to the poor in Gorontalo Province, as well as identifying the obstacles faced in its implementation. The background of this study is based on the principle of a state of law that guarantees the right to protection and access to justice for every citizen without discrimination, as regulated in Law Number 16 of 2011 concerning Legal Aid. This study uses an empirical legal method, with data collection techniques through observation, interviews, and documentation of OBHs active in the Gorontalo Province. The results of the study show that the role of OBHs is very significant in providing litigation and non-litigation legal assistance, as well as legal counseling to the poor. During the period 2022 to 2024, the number of cases handled and the budget absorbed showed a high increase and effectiveness, with a budget absorption rate of above 99%. However, there are several obstacles that hinder the effectiveness of services, such as budget limitations, lack of professional human resources, low legal literacy of the community, geographical constraints, administrative bureaucracy, and minimal support from local governments. Therefore, synergy is needed between the government, OBHs, and the community in strengthening an inclusive and equitable legal aid system.